تطورات القضية الصحراوية بين عامي (1963-1970) - RASHEED , ADRIS HUSSEIN; HAMDAN, ALI SALIH (Journal of Duhok University, 2023)
International pressure on France and Spain led to the granting of full independence to Morocco in 1956, followed by the independence of Algeria in 1962 to regulate friendly relations with the parties concerned on the basis of respect for international legitimacy and the organization of treaties that guarantee the rights of the two parties. To Morocco has delayed in one way or another these issues for the intervention of the United Nations to resolve these disputes by issuing a number of resolutions that called for calm and the implementation of its decisions regarding the complete withdrawal from Moroccan lands, and after Spain’s reneging on its promises, the Sahrawi resistance worked to continue its resistance in all available forms until its efforts paid off. In the restoration of Ifni and the great rapprochement between Morocco, Algeria and Mauritania, which had lands overlapping with those countries.